Step
*
3
of Lemma
qmul_wf
1. a10 : ℤ
2. a8 : ℤ
3. a9 : ℤ-o
4. (a10 * a9) = a8 ∈ ℤ
5. a5 : ℤ
6. a6 : ℤ-o
7. a2 : ℤ
8. a3 : ℤ-o
9. (a3 * a5) = (a2 * a6) ∈ ℤ
⊢ (a10 * a3 * a5 * a9) = (a10 * a2 * a6 * a9) ∈ ℤ
BY
{ (Mul ⌜a9 * a10⌝ (-1)⋅ THEN Auto) }
Latex:
Latex:
1. a10 : \mBbbZ{}
2. a8 : \mBbbZ{}
3. a9 : \mBbbZ{}\msupminus{}\msupzero{}
4. (a10 * a9) = a8
5. a5 : \mBbbZ{}
6. a6 : \mBbbZ{}\msupminus{}\msupzero{}
7. a2 : \mBbbZ{}
8. a3 : \mBbbZ{}\msupminus{}\msupzero{}
9. (a3 * a5) = (a2 * a6)
\mvdash{} (a10 * a3 * a5 * a9) = (a10 * a2 * a6 * a9)
By
Latex:
(Mul \mkleeneopen{}a9 * a10\mkleeneclose{} (-1)\mcdot{} THEN Auto)
Home
Index